Factors Influencing Self-rated Health Status in Middle-aged Women with Osteoporosis: Based on the 7th Korea National Health and Nutrition Examination Survey (Medico Legal Update, 2020)
Background/Objectives: The purpose of this study was to examine factors influencing self-rated health status in middle-aged women with osteoporosis in Korea.Method/Statistical Analysis: This study carried out secondary analysis using the available data of the 7th Korea National Health and Nutrition Examination Survey (2016-2018). Total subjects are 462 middle-aged women with osteoporosis. The data were analyzed by using descriptive statistics, multiple regression.Findings: Health-related quality of life (p = .045), comorbidity (hypertension, diabetes mellitus, dyslipidemia) (p = .001), body discomfort (p = .038), current alcohol drinking status (p